Moyamoya disease and pregnancy: case reports and criteria for successful vaginal delivery. Issue 4 (4th February 2015) - Sei, Kiguna; Sasa, Hidenori; Furuya, Kenichi
Key Clinical Message Based on our experience with seven deliveries (five cesarean and two vaginal deliveries) in five women with Moyamoya disease, we discussed the appropriate method of delivery and anesthesia for patients with Moyamoya disease. In certain conditions, women with Moyamoya disease can successfully undergo vaginal delivery.